Pengaruh Penggunaan Uang Elektronik Terhadap Perilaku Konsumtif Mahasiswa FEBI UNZAH - Nur Hafifa; Hayatul Millah; Nailin Nikmatul Maulidiyah (DPPM Universitas Pelita Bangsa, 2025)
This study aims to examine the influence of electronic money usage on the consumptive behavior of FEBI 21 students at Zainul Hasan Genggong University (UNZAH). The background of this research is based on the increasing use of electronic money among students, which is suspected to contribute to more impulsive and trend-driven consumption patterns. This research employed a quantitative method using simple linear regression analysis. The sample consisted of 30 respondents. The results show a very strong relationship between electronic money usage and consumptive behavior, indicated by a correlation coefficient (R) of 0.840 and a coefficient of determination (R²) of 0.706. This means that 70.6% of the variance in consumptive behavior can be explained by electronic money usage. The significance test (ANOVA) indicates that the regression model is statistically significant (sig. = 0.000), and the t-test also confirms that electronic money usage has a positive and significant effect on consumptive behavior (sig. = 0.000). In conclusion, electronic money usage has a significant influence on the consumptive behavior of FEBI 21 students at UNZAH.